Contribution A L’analyse De L’interface Strategie- Demarche Qualite Des Entreprises Marocaines Certifiees ISO 9001 - Mohamed Amine M'Barki; Sara Rbili (European Scientific Journal, ESJ, 2018)
The purpose of this paper is to clarify the relation between the strategic reflection and the quality process through a detailed analysis of the contributions of these two fields in a specific context which is the ISO 9001 certified Moroccan companies. Based on the organizational theories, the strategic schools, the key concepts of the TQM, and the contributions of 2015 version of the ISO 9001 standards we have proposed a performance-based unified theoretical integrative framework. From a methodological point of view, the coherence between the problematic and the data to which we have access and the nature of the studied phenomenon, has led us to prioritize a multi-method and sequential research approach. We have chosen to begin our empirical study by an exploratory study that was conducted through the use of an interview guide delivered to a sample of experts. This resulted in a more rewarding research model which in turn was subjected to tests by using structural equations as a part of the second empirical phase which was conducted on a sample of ISO 9001 certified Moroccan companies. The research has shed light on the emergence of a well differentiated typology of quality related behavior and a quite elaborated strategic reflection process. We have also confirmed the existence of an significant bilateral relation between the strategy and the quality, in accordance with an iterative process combining other factors (internal and external) that influence their transformation and their consequences. We have also highlighted the partial nature of the mediator role in the improvement of the performance concerning the alignment of the two disciplines